Exploring quranic narrative styles using interpersonal mood analysis based on a passage from Nuh story - Otay, Areej Ali; Abdul Jabar, Mohd Azidan; Hassan, Abd Rauf; Ismail, Muhd Zulkifli (Academy Publication, 2025)
This study employs interpersonal mood analysis to investigate the narrative styles utilized in translating Nuh's brief stories in Surah Al-Araf (Chapter Seven). This study examines the complex narrative techniques utilized in the Quran, concentrating on a particular passage from the story of Noah (Nuh). This study seeks to cast light on the interpersonal mood, a fundamental component of linguistic analysis, within the narrative structure of the Quran. The use of SFL as a methodological and analytic framework explores how the Quran uses language to convey interpersonal meaning, specifically in the context of the story of Nuh. Translating literary works entails conveying the original narrative style in the target language while preserving its essence. The qualitative content analysis is conducted on a sample of the translated texts of Prophet Nuh's short story by Saheeh International, with a focus on mood selection and the functional value of the language employed in the translations, as well as how the selected moods contribute to the overall narrative style and interpretation of the text. This analysis assists in comprehending how narrative style expresses their attitudes, intentions, and emotions via language. The findings of this study contribute to a greater comprehension of the Quranic narrative style by emphasizing the significance of interpersonal mood analysis as a method for deciphering the nuances of its storytelling techniques. This research not only enriches the field of Quranic linguistics but also offers valuable insights into the broader study of narrative discourse, nurturing a greater appreciation for the literary and communicative dimensions of religious texts.